Synchrotron Bragg diffraction imaging characterization of synthetic diamond crystals for optical and electronic power device applications. Issue 2 (29th March 2017) - Tran Thi, Thu Nhi; Morse, J.; Caliste, D.; Fernandez, B.; Eon, D.; Härtwig, J.; Barbay, C.; Mer-Calfati, C.; Tranchant, N.; Arnault, J. C.; Lafford, T. A.; Baruchel, J.
Abstract : Bragg diffraction imaging techniques are described, and their capabilities for studying the quality of diamond substrates and overgrown layers, and the surface damage caused by mechanical polishing, are illustrated by examples. Abstract : Bragg diffraction imaging enables the quality of synthetic single‐crystal diamond substrates and their overgrown, mostly doped, diamond layers to be characterized. This is very important for improving diamond‐based devices produced for X‐ray optics and power electronics applications. The usual first step for this characterization is white‐beam X‐ray diffraction topography, which is a simple and fast method to identify the extended defects (dislocations, growth sectors, boundaries, stacking faults, overall curvature etc. ) within the crystal. This allows easy and quick comparison of the crystal quality of diamond plates available from various commercial suppliers. When needed, rocking curve imaging (RCI) is also employed, which is the quantitative counterpart of monochromatic Bragg diffraction imaging. RCI enables the local determination of both the effective misorientation, which results from lattice parameter variation and the local lattice tilt, and the local Bragg position. Maps derived from these parameters are used to measure the magnitude of the distortions associated with polishing damage and the depth of this damage within the volume of the crystal. For overgrown layers, these maps also reveal the distortion induced by the incorporation of impurities such as boron, or the lattice parameter variations associated with the presence of growth‐incorporated nitrogen. These techniques are described, and their capabilities for studying the quality of diamond substrates and overgrown layers, and the surface damage caused by mechanical polishing, are illustrated by examples.